Plano de ações estratégicas para o laboratório de soldagem da Faculdade de Engenharia Mecânica - SANTOS, Danilo Silva (2020)
The purpose of this paper is to present a strategic action plan to the Mechanical Engineering Welding Laboratory management, represented by UFPA‟s Campus in Tucuruí. The proposal hinges upon the foundation on managing tools, that are applied to industrial spaces, such as the welding laboratory. These tools success, such as the 5S philosophy, the SWOT Matrix (Strengths, Weaknesses, Opportunities and Threats), the Balanced Score Card (BSC) and 5W2H, define them as an effective guiding mechanism of the welding laboratory managing actions, towards the service quality provided by the lab, both to the campus community and to the cities around. The result is the formulation of plans for each tool that develop in parallel in a four-year space with specific actions focused on excellence.